ANALISIS NILAI TAMBAH KERIPIK TALAS PRIANGAN PADA âINDUSTRI RUMAH TANGGA DARMATIAN PRODUCTâ DI KOTA PALU - Harnum, Harnum (AGROTEKBIS, 2016)
This study aims to determine how much added value on taro which has been processing into chips. Determination of the respondents in this studywas done by intentionally (purposive). Respondents who selected was the chief of